How to Make a Cake Rise : 500 Kitchen Tips and Tricks I Wish My Mother had Told Me - Mandal, Manidipa and Biggs, Fiona (Bath, U.K. Parragon, 2009)
COOKERY / FOOD & DRINK ETC. An invaluable guide for any household. With 500 handy tips and practical suggestions, this book provides an answer to every kitchen dilemma!
Include Index and Illustrations
Keywords: Creative ability